Parallel Nanometric 3D Tracking of Intracellular Gold Nanorods Using Multifocal Two-Photon Microscopy - van den Broek, Bram; Ashcroft, Brian; Oosterkamp, Tjerk H; van Noort, John (Nano letters, 2013)
We report a novel technique for long-term parallel three dimensional (3D)-tracking of gold nanorods in live cells with nanometer resolution. Gold nanorods feature a strong plasmon-enhanced two-photon luminescence, can be easily functionalized, and have been shown to be nontoxic. These properties make gold nanorods very suitable for in vivo two-photon luminescence microscopy. By rapid multifocal scanning, we combine the advantages of 3D molecular tracking methods using wide-field imaging with the advantages of two-photon microscopy. Isolated gold nanorods can be localized with a resolution of 4 nm in the xy-plane and 8 nm in the z-direction. The polarization-dependence of the two-photon luminescence signal can be used to resolve the angular orientation, even when two gold nanorods are separated by less than the diffraction limit. Individual nanorods in live U2OS cells could be followed in 3 dimensions for over 30 min, with a photon noise limited accuracy, and a time resolution of 50 ms in 2D and 500 ms in 3D.